Diagnosis and Treatment of Recto - Colonic Polyps - Sojo, Enrique; Estapé, Gonzalo; Falconi, Luis; de los Santos, Julio (Cirugía del Uruguay, 1980)
Review of case material of the Department of Digestive Fibroscopy in the Italian Hospital of Montevideo, comprising 243 patients suffering from isol'ated recto - colonic polyps, for the purpose of updating diagnostical and therapeutical methods conducive to greater effici.ncy in detection and non - invasive treatment of these lesions.